Análisis Exploratorio de Datos del Consumo del Servicio Público de Energía Eléctrica en Bogotá (2021)
Access to public services has a positive impact on the quality of life of citizens and is currently an intrinsic need of the human condition, impacting in essential factors such as food, health, education, among others. Do not however, socioeconomic conditions of the citizens, or economic problems or coverage of the supplier companies violate the fundamental right to have the basic public services. This research work focuses on seeking a relationship between the different open data variables available in the Single Information System (SUI) performing an analysis of the data of the residential public service of electrical energy of the city of Bogotá Colombia, in order to better understand the consumption behavior and paying subscribers and with a random sample of the data develop a model machine learning that helps predict potential delinquent candidates.